Surgical Excision of Benign Papillomas Diagnosed with Core Biopsy: A Community Hospital Approach - Eka Rozentsvayg; Kristen Carver; Sunita Borkar; Melvy Mathew; Sean Enis; Paul Friedman (Radiology Research and Practice)
Our goal was to assess the value of surgical excision of benign papillomas of the breast diagnosed on percutaneous core biopsy by determining the frequency of upgrade to malignancies and high risk lesions on a final surgical pathology. We reviewed 67 patients who had biopsies yielding benign papilloma and underwent subsequent surgical excision. Surgical pathology of the excised lesions was compared with initial core biopsy pathology results. 54 patients had concordant benign core and excisional pathology. Cancer (ductal carcinoma in situ and invasive ductal carcinoma) was diagnosed in five (7%) patients. Surgery revealed high-risk lesions in 8 (12%) patients, including atypical ductal hyperplasia, atypical lobular hyperplasia, and lobular carcinoma in situ. Cancer and high risk lesions accounted for 13 (19%) upstaging events from benign papilloma diagnosis. Our data suggests that surgical excision is warranted with core pathology of benign papilloma.